Aplicativo Android para mapeamento de rotas percorridas - Machado, Cleverson (2017)
Mobile devices are widely used. Statistical data confirm the high number of people who have these devices. The mobile applications are also many and diversified. The features offered by these devices, initially planned for mobile telephony, today include, among others, cameras, accelerometer, Global Positioning System (GPS), fingerprint reading, sensors and motion recognition. Considering the number of these devices and the many features they offer, it is proposed to develop an Android application for mapping routes traveled by the user. The initial use is intended for athletes and amateurs who walk unknown paths (trails, for example) and who can safely return from these trails and re-record them. This use does not apply only to places of difficult identification such as marshes, forests and desert regions, but can be used by tourists in unknown cities. However, the application, with the appropriate adjustments, can be applied to various commercial and personal uses that require registration of the path traveled. The application allows the user to specify the granularity of the route points (in distance or time).